Microvolt T-Wave Alternans Is Modulated by Acute Low-Level Tragus Stimulation in Patients With Ischemic Cardiomyopathy and Heart Failure - Kulkarni, Kanchan; Stavrakis, Stavros; Elkholey, Khaled; Singh, Jagmeet P.; Parks, Kimberly A.; Armoundas, Antonis A. (Frontiers in Physiology, 2021)
Aims: Microvolt T-wave alternans (TWA), an oscillation in T-wave morphology of the electrocardiogram (ECG), has been associated with increased susceptibility to ventricular tachy-arrhythmias, while vagus nerve stimulation has shown promising anti-arrhythmic effects in in-vivo and ex-vivo animal studies. We aimed to examine the effect of non-invasive, acute low-level tragus stimulation (LLTS) on TWA in patients with ischemic cardiomyopathy and heart failure. Methods: 26 patients with ischemic cardiomyopathy (LVEF <35%) and chronic stable heart failure, previously implanted with an AICD device with an atrial lead (dual chamber ICD or CRT-D), were enrolled in the study. Each patient sequentially received, (1) Sham LLTS (electrode on tragus, but no stimulation delivered) for 5 minutes; (2) Active LLTS at 2 different frequencies (5Hz and 20Hz, 15 minutes each); and (3) Active LLTS, during concomitant atrial pacing at 100bpm at 2 different frequencies (5Hz and 20Hz, 15 minutes each). LLTS was delivered through a transcutaneous electrical nerve stimulation device (pulse width 200 μs, frequency 5/20 Hz, amplitude 1 mA lower than the discomfort threshold). TWA burden was assessed using continuous ECG monitoring during sham and active LLTS in sinus rhythm, as well as during atrial pacing. Results: Right atrial pacing at 100bpm led to significantly heightened TWA burden compared to sinus rhythm, with or without LLTS. Acute LLTS at both 5 and 20Hz, during sinus rhythm led to a significant rise in TWA burden in the precordial leads (p<0.05). Conclusions: Acute LLTS results in a heart-rate dependent increase in TWA burden.